Heterogeneous presynaptic distribution of munc13 isoforms at retinal synapses and identification of an unconventional bipolar cell type with dual expression of munc13 isoforms: A study using munc13-exfp knock-in mice - Gierke, Kaspar; von Wittgenstein, Julia; Hemmerlein, Maike; Atorf, Jenny; Joachimsthaler, Anneka; Kremers, Jan; Cooper, Benjamin H.; Varoqueaux, Frederique; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2020)
Munc13 isoforms are constituents of the presynaptic compartment of chemical synapses, where they govern important steps in preparing synaptic vesicles for exocytosis. The role of Munc13-1,-2 and-3 is well documented in brain neurons, but less is known about their function and distribution among the neurons of the retina and their conventional and ribbon-type chemical synapses. Here, we examined the retinae of Munc13-1-,-2-, and-3-EXFP knock-in (KI) mice with a combination of immunocytochemistry, physiology, and electron microscopy. We show that knock-in of Munc13-EXFP fusion proteins did not affect overall retinal anatomy or synapse structure, but slightly affected synaptic transmission. By labeling Munc13-EXFP KI retinae with specific antibodies against Munc13-1,-2 and-3, we found that unlike in the brain, most retinal synapses seem to operate with a single Munc13 isoform. A surprising exception to this rule was type 6 ON bipolar cells, which expressed two Munc13 isoforms in their synaptic terminals, ubMunc13-2 and Munc13-3. The results of this study provide an important basis for future studies on the contribution of Munc13 isoforms in visual signal processing in the mammalian retina.
CRIS-Team Scopus Importer:2020-11-06
Keywords: BrMunc13-2; Conventional synapse; Munc13-1; Munc13-3; Retina; Ribbon synapse; Type 6 ON bipolar cell; UbMunc13-2